Internal Control System Effectiveness: The Impact of Human Resource Competence and Budget Target Clarity - Amaliah Kesuma; Rita Martini; Yuliana Sari (Eduvest - Journal of Universal Studies, 2026)
This study focusses on the impact of human resource (HR) competency and budget target clarity on the efficacy of the internal control system (ICS). The background of this research is derived from findings correlated to incapacities in the ICS in the Audit Result Report of Palembang City issued by the Supreme Audit Institution of Indonesia (BPK). This study applies a quantitative approach with primary data as the data source. The hypothesis testing tool used is Statistical Product and Service Solutions version 29 application. The data analyze applies multiple linear regression method. The sample collection method in this research is purposive sampling. The outcomes present that HR competence and budget target clarity have a significant and positive impact on the effectiveness of the ICS. This research gives important inferences for local governments in strengthening the internal control system as a whole, both in terms of structure, procedures, and internal monitoring mechanisms that are able to detect and prevent potential deviations.